Vietnam in 1948: An International History Perspective - Ang Cheng Guan (Kajian Malaysia, 2009)
This paper revisits the year 1948 in an effort to determine whether 1948 can be considered the starting point of the Cold War in Vietnam. Historical periodisation is a tricky affair, and it is often difficult to pinpoint the genesis of events. By reconstructing the political and military developments in 1948 from the indigenous perspective as well as from regional and international perspectives that directly impinged on Vietnam, I hope to ascertain whether Vietnam’s war of liberation was indeed transformed into a “Cold War” from 1948 onwards—in other words, whether it was in 1948 that the Vietnamese struggle assumed an ideological complexion that shifted from nationalist/anti-colonial sentiment to include communist/anti-capitalist sentiment as well.1 Before we embark on our consideration of the year 1948, it is useful to recount in broad brush-strokes some key developments in Vietnam leading up to 1948. In order to put the year 1948 in context, it is also necessary to consider in some detail two key developments in 1947